Development of novel bioassays to detect soluble and aggregated Huntingtin proteins on three technology platforms. Issue 1 (5th January 2021) - Landles, Christian; Milton, Rebecca E; Jean, Alexandre; McLarnon, Stuart; McAteer, Sean J; Taxy, Bridget A; Osborne, Georgina F; Zhang, Chuangchuang; Duan, Wenzhen; Howland, David; Bates, Gillian P
Abstract: Huntington's disease is caused by a CAG / polyglutamine repeat expansion. Mutated CAG repeats undergo somatic instability, resulting in tracts of several hundred CAGs in the brain; and genetic modifiers of Huntington's disease have indicated that somatic instability is a major driver of age of onset and disease progression. As the CAG repeat expands, the likelihood that exon 1 does not splice to exon 2 increases, resulting in two transcripts that encode full-length huntingtin protein, as well as the highly pathogenic and aggregation-prone exon 1 huntingtin protein. Strategies that target the huntingtin gene or transcripts are a major focus of therapeutic development. It is essential that the levels of all isoforms of huntingtin protein can be tracked, to better understand the molecular pathogenesis, and to assess the impact of huntingtin protein-lowering approaches in preclinical studies and clinical trials. Huntingtin protein bioassays for soluble and aggregated forms of huntingtin protein are in widespread use on the homogeneous time-resolved fluorescence and Meso Scale Discovery platforms, but these do not distinguish between exon 1 huntingtin protein and full-length huntingtin protein. In addition, they are frequently used to quantify huntingtin protein levels in the context of highly expanded polyglutamine tracts, for which appropriate protein standards do not currently exist. Here, we set out to develop novel huntingtin protein bioassays to ensure that all soluble huntingtin protein isoforms could be distinguished. We utilized the zQ175 Huntington's disease mouse model that has ∼190 CAGs, a CAG repeat size for which protein standards are not available. Initially, 30 combinations of six antibodies were tested on three technology platforms: homogeneous time-resolved fluorescence, amplified luminescent proximity homogeneous assay and Meso Scale Discovery, and a triage strategy was employed to select the best assays. We found that, without a polyglutamine-length-matched standard, the vast majority of soluble mutant huntingtin protein assays cannot be used for quantitative purposes, as the highly expanded polyglutamine tract decreased assay performance. The combination of our novel assays, with those already in existence, provides a tool-kit to track: total soluble mutant huntingtin protein, soluble exon 1 huntingtin protein, soluble mutant huntingtin protein (excluding the exon 1 huntingtin protein) and total soluble full-length huntingtin protein (mutant and wild type). Several novel aggregation assays were also developed that track with disease progression. These selected assays can be used to compare the levels of huntingtin protein isoforms in a wide variety of mouse models of Huntington's disease and to determine how these change in response to genetic or therapeutic manipulations. Abstract : Landles et al. report that they have developed novel bioassays to provide a tool kit for the detection of soluble and aggregated isoforms of the HTT protein in tissue lysates from mouse models of Huntington's disease on three bioassay platforms. Graphical Abstract: